Experimental Set-up for Investigation of Internal Erosion in Geosynthetic Clay Liners - Budihardjo, Mochamad; Chegenizadeh, Amin; Nikraz, Hamid (Planetary Scientific Research Centre, 2012)
Some factors that can potentially reduce the performance of geosynthetic clay liners (GCLs) and trigger an internal erosion of the GCL are high gradient, subgrade and confining pressure. Previous studies mainly investigated the internal erosion occurrence by monitoring the hydraulic conductivity with water flow coming from above. In this research, the opposite directions of water pressure were also applied to the sample. This experiment also sought some visual evidences and behavior of bentonite migration. The result indicated that internal erosion did not occur in the GCLs sample, however further investigation should be carried out since a sidewall leakage happened during the test.